2014
DOI: 10.1007/s10584-014-1234-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of evapotranspiration and water availability to the changing climate in Northern Eurasia

Abstract: Northern Eurasian ecosystems play an important role in the global climate system. Northern Eurasia (NE) has experienced dramatic climate changes during the last half of the 20th century and to present. To date, how evapotranspiration (ET) and water availability (P-ET, P: precipitation) had changed in response to the climatic change in this region has not been well evaluated. This study uses an improved version of the Terrestrial Ecosystem Model (TEM) that explicitly considers ET from uplands, wetlands, water b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…The same declining trends were also found in other regions throughout the world, such as New Zealand (from the 1970s to the early 2000s), India , and parts of China [12][13][14]. However, an increasing trend in ET 0 was identified in other regions from the 1960s to early 2000s, such as Iran , Northern Eurasia , and parts of Romania (1961Romania ( -2007 [3,15,16].…”
Section: Introductionsupporting
confidence: 65%
“…The same declining trends were also found in other regions throughout the world, such as New Zealand (from the 1970s to the early 2000s), India , and parts of China [12][13][14]. However, an increasing trend in ET 0 was identified in other regions from the 1960s to early 2000s, such as Iran , Northern Eurasia , and parts of Romania (1961Romania ( -2007 [3,15,16].…”
Section: Introductionsupporting
confidence: 65%
“…Shikano et al 23 estimated total evaporation for Chany, a shallow endorheic lake in Southwest Siberia close to BNNP area, to amount to 714 mm (1994)(1995)(1996)(1997)(1998)(1999). Two recent studies focused on North Eurasia's ET 36,37 ; based on ecosystem and remote sensing modeling efforts they found open-water evaporation estimates (using the Penman model) about 800 mm year …”
Section: 9mentioning
confidence: 99%
“…Shadmani et al (2012) and Kousari et al (2013) reported that a majority of weather stations in Iran present a negative trend but others show an increase in ET o trends. A study for Northern Eurasia detected significant decreasing trends as more important than the positive ones (Liu et al 2014). For Romania (Croitoru et al 2013) positive trends were detected for most of locations.…”
mentioning
confidence: 91%